Public sociology vs. the market - Burawoy, Michael (Socio-Economic Review, 2007)
Building on Karl Polanyi's theory of a societal reaction to the unregulated exchange of what he called fictitious commodities—labour, money and land—this paper links the history of sociology to the history of the market. If the first wave of marketization in the nineteenth century dwelt on the commodification of labour, prompting utopian sociologies, and the second wave of marketization of the twentieth century was provoked by the commodification of money, generating national policy sociologies, then the third wave of marketization that began in the last quarter of the twentieth century includes the commodification of the environment (land, air, water), and calls for public sociologies of a global dimension.
Sociology
Keywords: commercial products; fictitious commodities; government policy; history of sociology; markets - social aspects; publicity - social aspects; social theory; socioeconomics; utopian socialism

The Future of Sociology - Burawoy, Michael (Sociological Bulletin, 2007)
Like a hurricane, third-wave marketisation is picking up velocity and destroying societies in its path, destroying the very grounds upon which sociology grows. Sociology and humanity have a common interest in upholding civil society, and keeping state and market at bay. Working with Karl Polanyi's The Great Transformation, I diagnose three waves of marketisation associated with the commodification of labour, money and land, generating counter-movements at local, national and global levels. I argue that sociology is reshaped with each wave: in the first, it is utopian; in the second, it is driven by policy concerns; whereas emerging with the third wave marketisation is public sociology. The possibilities and challenges of public sociology as well as its relation to policy, critical and professional sociology are the subjects of this paper.
Sociology
Keywords: commodification; countermovement; government policy; humanity; labor; marketisation; markets; nature; public sociology; social sciences; societies; sociology; utopian socialism